Exploring Undergraduate Students’ Perceptions of Using Pronunroid-Ipa in Pronunciation Learning - Rizka Putri Nurulia (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Learning English pronunciation is important because it is essential for communication, especially for non-native speakers. People who are used to speaking primarily in their mother tongue will find it difficult when they speak English, which can affect their pronunciation (Borisovna, 2022; Ardini et al., 2022). By learning pronunciation, even if speakers have different language backgrounds, good pronunciation can lead to clear conversations and a stronger connection to meaning. Nowadays, most instructional media used in the teaching and learning process are digital. One of the tools that can support education in the digital era related to pronunciation learning is Pronunroid-IPA.
Repo 24 Juni 2026_ Rudy K Approved by Teddy
Keywords: Perceptions of Using Pronunroid